Rural and microfinance in the lower Mekong region policies, institutions, and market outcomes - Nguyen, Binh T.; Vogel, Robert (Mandaluyong City Asian development Bank, 2011)
"This study examines progress in rural and microfinance in Cambodia, the Lao People's Democratic Republic, and Viet Nam over the past decade, in comparison with industry standards set by international best practices. The study focuses on the policy environment, including regulatory norms and their implementation, as well as support provided to financial infrastructure, and the impact of this environment on the development and performance of institutions providing rural and microfinance services. This examination helps guide government and international development agencies as to which types of interventions can be most supportive of efficient and sustainable institutions that provide financial products and services to the poor, especially those in rural areas."--Provided by publisher.
Recent developments in rural and microfinance -- Cambodia, broadening services and expanding outreach -- Lao People's Democratic Republic, continuing reforms and capacity building to create a robust sector -- Viet Nam, reducing government dominance and formalizing microfinance -- Conclusions and recommendations, major similarities and differences among the three countries.
"Publication stock no. BKK102560"--T.p. verso.
Includes bibliographical references (p. 120-126).
Keywords: Loans -- Government policy -- Southeast Asia; Microfinance -- Government policy -- Southeast Asia